MAINSTREAMING GREEN SKILLS THROUGH LIFE SKILLS EDUCATION: A STUDY ON AWARENESS AND IMPLEMENTATION - BERNARD, MRS. JASMINE; RM , DR. SAM DEVA ASIR (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Green skills are the technical skills, knowledge, values and attitudes needed in the workforce to develop and support sustainable social, economic and environmental outcomes in business, industry and the community. Aim: The aim is to examine their knowledge, mastery, application, and development of green skills essential for sustainable development and growth. Purpose: The purpose of the study is to understand the level of awareness and understanding of green skills among postgraduate students and suggest few recommendations to enhance green skills. Method: The researcher has adopted Descriptive Research Design. Convenient sampling method was used select the samples. The sample size for the study was 108. The respondents were administered with the self-prepared questionnaire with four dimensions. The dimensions are Understanding, Mastery Application and Development of Green Skills. Findings: Despite postgraduate students exhibiting a fundamental comprehension and even proficiency in green skills, a notable disparity exists in their implementation of these competences in both personal and professional contexts. Conclusion: This underscores the need for life skills into education systems to move beyond knowledge transmission and focus on experiential, interdisciplinary approaches that bridge the gap between knowing and doing.